2015
DOI: 10.1039/c5ee02024g
|View full text |Cite
|
Sign up to set email alerts
|

Macrokinetic effects in perhydro-N-ethylcarbazole dehydrogenation and H2productivity optimization by using egg-shell catalysts

Abstract: This contribution deals with pore diffusion influences on the dehydrogenation kinetics of perhydro-N-ethylcarbazole (H12-NEC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Although there are many studies about the dehydrogenation reaction from calculations and experiments [20][21][22][23][24][25][26][27][28], the dehydrogenation reaction is still the key to limit its large-scale application, especially, the development of dehydrogenation catalysts with outstanding activity and stability is the hotspot of current research. A large number of dehydrogenation catalysts have been extensively investigated, including homogeneous catalysts and the heterogeneous catalysts [29][30][31][32][33][34][35]. For the homogeneous catalysts, Wang et al firstly reported the synthesis of homogeneous Ir-complex catalysts and explored its performance for the hydrogen release of dodecahydro-N-ethylcarbazole at 473 K but the dehydrogenation results were unsatisfactory [34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are many studies about the dehydrogenation reaction from calculations and experiments [20][21][22][23][24][25][26][27][28], the dehydrogenation reaction is still the key to limit its large-scale application, especially, the development of dehydrogenation catalysts with outstanding activity and stability is the hotspot of current research. A large number of dehydrogenation catalysts have been extensively investigated, including homogeneous catalysts and the heterogeneous catalysts [29][30][31][32][33][34][35]. For the homogeneous catalysts, Wang et al firstly reported the synthesis of homogeneous Ir-complex catalysts and explored its performance for the hydrogen release of dodecahydro-N-ethylcarbazole at 473 K but the dehydrogenation results were unsatisfactory [34].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, in this work, for the first time, we have utilized an alcohol reduction method to construct CNT-supported Pd NPs (Pd/CNTs) as the catalyst for hydrogen generation from dodecahydro-N- A large number of dehydrogenation catalysts have been extensively investigated, including homogeneous catalysts and the heterogeneous catalysts [29][30][31][32][33][34][35]. For the homogeneous catalysts, Wang et al firstly reported the synthesis of homogeneous Ir-complex catalysts and explored its performance for the hydrogen release of dodecahydro-N-ethylcarbazole at 473 K but the dehydrogenation results were unsatisfactory [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12]. In the flamelet scenario, the diffusion tangential to the mixture-fraction iso-surface is negligible and heat is diffused away from the surface in the normal direction [25]. The propagation of an edge-flame towards the unburned region will result in the heat being diffused away from the surface in the normal direction and diffused towards closing the hole in the plane of mixture-fraction iso-surface,…”
Section: Extinction Holes Identificationmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Cost: the initial cost of setting up RES is high. [11][12][13][14][15] Storage: the most commonly used energy storage medium is batteries; however, with the increasing demand, especially for electric vehicles, mineral sources (such those of Li, which plays an integral role in batteries) are continually being depleted, hence leading to increasing production costs. 1,11,12,[15][16][17] Transportation: transportation is closely associated with issues of storage; safe transportation requires safe energy storage technologies.…”
Section: Introductionmentioning
confidence: 99%